Pashto phonology an evaluation of the relationship between syllable structure and word order - Khan, Muhammad Kamal (Cambridge Scholars Publisher, 2020)
The book provides a detailed analysis of the relationship between syllable structure and word order, a long-standing correlation in typological linguistics which has been previously described as an implicational universal. It presents data from Pashto (an Eastern-Iranian language spoken mainly in Pakistan and Afghanistan), and explores consonant clusters and the basic word order of the language.It begins by introducing the Pashto language, before going on to highlight the word order typology and language universals, followed by a detailed analysis of its syllable structure and basic word order.